Development of indexer considering tag weighting for XML document / Masliana Wahid @ Buang - Wahid @ Buang, Masliana (2005)
Information retrieval makes the retrieval of document or collection of data in the storage media more efficient, effective, relevant, faster and more reliable than before. Such indexing techniques may influence the effectiveness of retrieval itself. The extension component within the indexing structure may also influence the performance of the retrieval process. This research is concerns to develop a prototype for indexing algorithm considering tag weighting for the XML document and also to test the indexer with the existing document, hi order to perform efficient retrieval on documents, appropriate index structure or algorithm must be used which include the structural information. This research is used the inverted file method for the indexing techniques to develop the indexing algorithm of the FTMSK official letter. The relevancy of the document for the retrieval by usmg the algorithm has been successfiil achieved and it can prove that the prototype can increase the relevancy of document retrieval. COPYRIGHT ©